Composite filler and its manufacturing method

The composite filler with a core-shell structure, featuring a carbon or metal core and a fumed oxide shell, addresses the insulation and heat dissipation challenges in high-voltage electronic devices by achieving enhanced thermal conductivity and electrical insulation properties.

JP7661456B1Active Publication Date: 2025-04-14NIPPON AEROSIL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023206607
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-04-14
Estimated Expiration
2043-12-07

AI Technical Summary

Technical Problem

Existing thermally conductive particles are insufficient for electronic devices with increased voltage and current, as they lack adequate electrical insulation properties.

Method used

A composite filler with a core-shell structure is developed, where the core is made of carbon, metal, zinc oxide, or zirconium oxide, and the shell is formed by adhering fumed oxide particles to the core using a dry ball mill. This structure enhances both thermal conductivity and electrical insulation.

Benefits of technology

The composite filler achieves thermal conductivity of 0.075 W/m·K or more and volume resistivity of 1.0×10^5 Ω·cm or more, along with a breakdown voltage of 1 kV/mm or more, effectively addressing the insulation and heat dissipation needs of high-voltage and high-current electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661456000001_ABST
    Figure 0007661456000001_ABST
Patent Text Reader

Abstract

Provided is a composite filler that has heat dissipation properties (thermal conductivity) and also has higher electrical insulation properties than conventional ones. [Solution] This is a composite filler that forms a core-shell structure consisting of a core material made of carbon, metal, zinc oxide or zirconium oxide, and a shell material attached to the surface of the core material. The shell material is formed by mixing fumed oxide particles and the core material in a dry ball mill, so that the fumed oxide particles are attached to part or all of the surface of the core material. The fumed oxide particles are particles in which spherical primary particles are aggregated and fused together in a beaded shape to form bulky aggregated particles, and these aggregated particles are transformed into agglomerated particles. In the composite filler, the core material is 30 to 85 vol. %, the shell material is 15 to 70 vol. %, the thermal conductivity is 0.075 W / m K or more, and the volume resistivity is 1.0 × 10 5 The dielectric strength is Ω·cm or more, and the dielectric breakdown voltage is 1 kV / mm or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite filler having a heat dissipating core and an electrically insulating shell attached to the surface of the core, and a method for producing the same. [Background technology]

[0002] In recent years, electronic devices used in electric vehicles and the like have become higher in voltage and current. As a result, the amount of heat generated by these electronic devices has also increased, and one of the major issues is how to dissipate this heat. Parts used in these electronic devices are required to have high heat dissipation performance, i.e., thermal conductivity, as well as high electrical insulation from the viewpoint of reliability.

[0003] Conventionally, as a material having thermal conductivity and electrical insulation, thermally conductive particles including a composite core and an insulating material coating at least a part of the composite core, and a method for producing the same have been disclosed (see, for example, Patent Document 1 (Claim 1, Claim 13, Paragraphs

[0021] ,

[0028] ,

[0037] ,

[0038] ,

[0049] ,

[0053] ,

[0058] ,

[0097] , and

[0098] )). The thermally conductive particles and a resin are mixed to produce a resin composition, which is then molded, and the molded product is used as a part of the electronic device.

[0004] The composite core includes a plurality of thermally conductive core particles and an organic binder binding the core particles together, the core particles being selected from the group consisting of metal particles, ceramic particles, carbon-based particles, and mixtures thereof, and the insulating material being selected from the group consisting of aluminum oxide (alumina), zinc oxide, talc, magnesium oxide, silicon dioxide, boehmite, boron nitride, mica, aluminum nitride, silicon nitride, zinc sulfide, sericite, and mixtures thereof.

[0005] The method for producing the thermally conductive particles includes mixing a plurality of core particles and an organic binder by compressive shear mixing to bond and mix the core particles with the organic binder to form a composite core, and then mixing the composite core and an insulating material by compressive shear mixing to at least partially coat the composite core with the insulating material.

[0006] The metal particles of the core particle include copper, silver, nickel, aluminum, or alloys thereof, and the carbon-based particles of the core particle include graphite, carbon nanotubes, fullerenes, graphene, carbon black, glassy carbon, carbon fiber, amorphous carbon, boron carbide, or mixtures thereof.

[0007] The thermally conductive particles thus constructed have a thermal conductivity of at least 1×10 when measured with an applied voltage of 500 V on a cylinder of the thermally conductive particles having a diameter of 10 mm and a height of 3.0 mm. 4 Ω cm~1×10 10 It is characterised by exhibiting a volume resistivity in the Ω·cm range. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Special Publication No. 2017-504177 Summary of the Invention [Problem to be solved by the invention]

[0009] The thermally conductive particles shown in Patent Document 1 have an insulation index of 1×10 4 Ω cm~1×10 10 The thermally conductive particles have a volume resistivity in the range of Ω·cm. However, the electrical insulation properties of these particles are insufficient for use as materials and components in electronic devices that require higher voltages and currents, and materials with even higher electrical insulation properties are needed.

[0010] An object of the present invention is to provide a composite filler having heat dissipation properties (thermal conductivity) and higher electrical insulation than conventional ones, and a method for producing the same. [Means for solving the problem]

[0011] A first aspect of the present invention is a composite filler that forms a core-shell structure composed of a core material made of carbon, metal, zinc oxide or zirconium oxide and a shell material attached to the surface of the core material, the shell material being formed by mixing fumed oxide particles and the core material in a dry ball mill, the fumed oxide particles being attached to a part or all of the surface of the core material, the fumed oxide particles being particles formed by forming bulky aggregate particles by agglomerating and fusing spherical primary particles in a beaded shape, and the aggregate particles being changed into agglomerated particles, and when the composite filler is taken as 100 volume %, the core material is in the range of 30 volume % to 85 volume %. The shell material is in the range of 15% to 70% by volume, the thermal conductivity measured under the maximum compressive load condition (2400.0 gF) using a thermal conductivity measuring device TRIDENT and a compression test accessory (CTA) manufactured by C-Therm is 0.075 W / m K or more, and the volume resistivity measured using a high resistance / resistivity meter "Hiresta-UX" (manufactured by Mitsubishi Chemical Analytech Co., Ltd.: model number "MCP-HT800") or a low resistance / resistivity meter "Loresta-GX" (manufactured by Mitsubishi Chemical Analytech Co., Ltd.: model number "MCP-T700") and a powder resistivity measurement system (manufactured by Mitsubishi Chemical Analytech Co., Ltd.: model number "MCP-PD-51") is 1.0 x 10 5 It is characterized by having a dielectric strength of Ω·cm or more and a dielectric breakdown voltage of 1 kV / mm or more as measured using an AC Withstand Voltage Tester 7473 manufactured by Keisoku Gijutsu Kenkyusho Co., Ltd.

[0012] A second aspect of the present invention is the invention based on the first aspect, wherein the carbon core material is graphite, ketjen black, graphite or carbon black, and the metal core material is copper, zinc, tin, nickel, aluminum or stainless steel.

[0013] A third aspect of the present invention is an invention based on the first aspect, wherein the particle size of the composite filler is in the range of 1 μm to 300 μm as measured by a volume distribution of the composite filler using a laser diffraction particle size distribution meter.

[0014] A fourth aspect of the present invention is the invention based on the first aspect, wherein the fumed oxide particles are fumed silica particles or fumed alumina particles.

[0015] A fifth aspect of the present invention is a method for producing a composite filler, which comprises mixing fumed oxide particles in which spherical primary particles are aggregated and fused together in a beaded shape to form bulky aggregated particles, and the aggregated particles are changed into agglomerate particles, with a core material made of carbon, metal, zinc oxide or zirconium oxide in a volume ratio of fumed oxide particles:core material=30 to 85:70 to 15 in a dry ball mill, thereby forming a core-shell structure in which the fumed oxide particles are attached as a shell material to a part or all of the surface of the core material, wherein the fumed oxide particles are particles in which spherical primary particles are aggregated and fused together in a beaded shape to form bulky aggregated particles, and the aggregated particles are changed into agglomerate particles. Effect of the Invention

[0016] The composite filler according to the first aspect of the present invention is obtained by mixing and adhering a shell material constituted by particles in which spherical primary particles are aggregated and fused together in a beaded shape to form bulky aggregated particles, and these aggregated particles are transformed into agglomerated particles, to the surface of a core material made of carbon, metal, zinc oxide or zirconium oxide in a dry ball mill, and by the core material being in the range of 30% by volume to 85% by volume and the shell material being in the range of 15% by volume to 70% by volume, when the composite filler is taken as 100% by volume, the thermal conductivity is 0.075 W / m K or more and the volume resistivity is 1.0×10 5 It has the characteristics of having a dielectric strength of Ω·cm or more and a dielectric breakdown voltage of 1 kV / mm or more.

[0017] The composite filler according to the second aspect of the present invention has high thermal conductivity since the carbon core material is graphite, ketjen black, graphite or carbon black, and the metal core material is copper, zinc, tin, nickel, aluminum or stainless steel.

[0018] The composite filler according to the third aspect of the present invention has a particle size in the range of 1 μm to 300 μm, and therefore has the characteristic that when this composite filler is mixed with a resin to produce a resin composition, the resin composition can be easily molded.

[0019] In the composite filler according to the fourth aspect of the present invention, the fumed oxide particles are fumed silica particles or fumed alumina particles, and therefore when attached to the surface of the core material as a shell material, the electrical insulation of the composite filler is improved.

[0020] In the composite filler manufacturing method according to the fifth aspect of the present invention, the composite filler is manufactured by mixing fumed oxide particles, which are formed by forming bulky aggregated particles by agglomerating and fusing spherical primary particles in a beaded shape and changing the aggregated particles into agglomerated particles, with a core material made of carbon, metal, zinc oxide or zirconium oxide in a volume ratio of fumed oxide particles:core material=30-85:70-15 in a dry ball mill, so that the fumed oxide particles adhere to the surface of the core material as a shell material in a relatively simple manner. The composite filler manufactured in this way has the features of having heat dissipation properties (thermal conductivity) and higher electrical insulation than conventional materials. [Brief description of the drawings]

[0021] [Figure 1] This is a schematic cross-sectional view of a composite filler in which spherical primary particles are aggregated and fused together in a beaded shape to form bulky aggregated particles on the surface of a core material in an embodiment of the present invention, and fumed oxide particles that have changed from these aggregated particles to agglomerated particles are attached. [Diagram 2]FIG. 2 is a diagram showing a state in which the agglomerated particles shown in FIG. 1 are changed from the agglomerated particles shown in FIG. 1 into bulky agglomerated particles formed by agglomeration and fusion of spherical primary particles in a beaded shape. [Diagram 3] FIG. 2 is a scanning electron microscope (SEM) photograph showing aggregate particles, which are the smallest particle form formed by sintering primary silica particles. [Figure 4] FIG. 4 is a scanning electron microscope (SEM) photograph showing an agglomerated particle formed by gathering the aggregated particles shown in FIG. 3. [Figure 5a] FIG. 2 is a graph showing a particle size distribution curve of the Sn powder in Example 1 superimposed on a particle size distribution curve of a composite filler obtained by mixing the Sn powder and fumed alumina particles in a dry ball mill. [Figure 5b] FIG. 2 is a scanning electron microscope (SEM) photograph of the Sn powder of Example 1. [Figure 5c] FIG. 2 is a scanning electron microscope (SEM) photograph of the composite filler of Example 1. [Figure 6a] FIG. 1 is a graph showing a particle size distribution curve of the Zn powder in Example 2 superimposed on a particle size distribution curve of a composite filler obtained by mixing the Zn powder and fumed alumina particles in a dry ball mill. [Figure 6b] FIG. 2 is a scanning electron microscope (SEM) photograph of the Zn powder of Example 2. [Figure 6c] FIG. 2 is a scanning electron microscope (SEM) photograph of the composite filler of Example 2. [Figure 7a] FIG. 13 is a graph showing a particle size distribution curve of the Ni powder in Example 3 superimposed on a particle size distribution curve of a composite filler obtained by mixing the Ni powder and fumed alumina particles in a dry ball mill. [Figure 7b] FIG. 1 is a scanning electron microscope (SEM) photograph of the Ni powder of Example 3. [Figure 7c] FIG. 1 is a scanning electron microscope (SEM) photograph of the composite filler of Example 3. [Figure 8a] FIG. 1 is a graph showing a particle size distribution curve of the SUS powder in Example 4 superimposed on a particle size distribution curve of a composite filler obtained by mixing the SUS powder and fumed alumina particles in a dry ball mill. [Figure 8b]FIG. 1 is a scanning electron microscope (SEM) photograph of the SUS powder of Example 4. [Figure 8c] FIG. 1 is a scanning electron microscope (SEM) photograph of the composite filler of Example 4. [Figure 9a] FIG. 13 is a graph showing a particle size distribution curve of the ZnO powder in Example 5 superimposed on a particle size distribution curve of a composite filler obtained by mixing the ZnO powder and fumed alumina particles in a dry ball mill. [Figure 9b] FIG. 1 is a scanning electron microscope (SEM) photograph of the ZnO powder of Example 5. [Figure 9c] FIG. 1 is a scanning electron microscope (SEM) photograph of the composite filler of Example 5. [Figure 10a] FIG. 13 is a graph showing a particle size distribution curve of the Cu powder in Example 6 superimposed on a particle size distribution curve of a composite filler obtained by mixing the Cu powder and fumed alumina particles in a dry ball mill. [Figure 10b] FIG. 1 is a scanning electron microscope (SEM) photograph of the Cu powder of Example 6. [Figure 10c] FIG. 1 is a scanning electron microscope (SEM) photograph of the composite filler of Example 6. [Figure 11a] FIG. 13 is a graph showing a particle size distribution curve of the Cu powder in Example 7 superimposed on a particle size distribution curve of a composite filler obtained by mixing the Cu powder and fumed alumina particles in a dry ball mill. [Figure 11b] FIG. 1 is a scanning electron microscope (SEM) photograph of the Cu powder of Example 7. [Figure 11c] FIG. 1 is a scanning electron microscope (SEM) photograph of the composite filler of Example 7. [Figure 12a] FIG. 13 is a graph showing a particle size distribution curve of the Cu powder in Example 8 superimposed on a particle size distribution curve of a composite filler obtained by mixing the Cu powder and fumed alumina particles in a dry ball mill. [Figure 12b] FIG. 1 is a scanning electron microscope (SEM) photograph of the Cu powder of Example 8. [Figure 12c] FIG. 1 is a scanning electron microscope (SEM) photograph of the composite filler of Example 8. [Figure 13a]FIG. 13 is a graph showing a particle size distribution curve of the Cu powder in Example 9 superimposed on a particle size distribution curve of a composite filler obtained by mixing the Cu powder and fumed alumina particles in a dry ball mill. [Figure 13b] FIG. 1 is a scanning electron microscope (SEM) photograph of the Cu powder of Example 9. [Figure 13c] FIG. 1 is a scanning electron microscope (SEM) photograph of the composite filler of Example 9. [Figure 14a] FIG. 13 is a graph showing a particle size distribution curve of the Cu powder in Example 10 superimposed on a particle size distribution curve of a composite filler obtained by mixing the Cu powder and fumed alumina particles in a dry ball mill and then subjecting them to a surface treatment. [Figure 14b] FIG. 1 is a scanning electron microscope (SEM) photograph of the Cu powder of Example 10. [Figure 14c] FIG. 1 is a scanning electron microscope (SEM) photograph of the composite filler of Example 10. [Figure 15a] FIG. 13 is a graph showing a particle size distribution curve of the Al powder in Example 11 superimposed on a particle size distribution curve of a composite filler obtained by mixing the Al powder and fumed alumina particles in a dry ball mill. [Figure 15b] FIG. 1 is a scanning electron microscope (SEM) photograph of the Al powder of Example 11. [Figure 15c] FIG. 11 is a scanning electron microscope (SEM) photograph of the composite filler of Example 11. [Figure 16a] FIG. 13 is a graph showing a particle size distribution curve of the ZrO powder in Example 12 superimposed on a particle size distribution curve of a composite filler obtained by mixing the ZrO powder and fumed alumina particles in a dry ball mill. [Figure 16b] FIG. 1 is a scanning electron microscope (SEM) photograph of the ZrO powder of Example 12. [Figure 16c] FIG. 12 is a scanning electron microscope (SEM) photograph of the composite filler of Example 12. [Figure 17a] FIG. 13 is a graph showing a particle size distribution curve of the graphite powder in Example 13 superimposed on a particle size distribution curve of a composite filler obtained by mixing the graphite powder and fumed silica particles in a dry ball mill. [Figure 17b]FIG. 1 is a scanning electron microscope (SEM) photograph of the graphite powder of Example 13. [Figure 17c] FIG. 13 is a scanning electron microscope (SEM) photograph of the composite filler of Example 13. [Figure 18a] FIG. 1 is a graph showing a particle size distribution curve of the Cu powder in Comparative Example 1 superimposed on a particle size distribution curve of a composite filler obtained by mixing the Cu powder and fumed silica particles by dry hand mixing. [Figure 18b] FIG. 2 is a scanning electron microscope (SEM) photograph of the Cu powder of Comparative Example 1. [Figure 18c] FIG. 2 is a scanning electron microscope (SEM) photograph of the composite filler of Comparative Example 1. [Figure 19a] FIG. 13 is a graph showing a particle size distribution curve of the Cu powder in Comparative Example 2 superimposed on a particle size distribution curve of a composite filler obtained by mixing the Cu powder and fumed silica particles in a dry rotation-revolution type mixer. [Figure 19b] FIG. 2 is a scanning electron microscope (SEM) photograph of the Cu powder of Comparative Example 2. [Figure 19c] FIG. 1 is a scanning electron microscope (SEM) photograph of the composite filler of Comparative Example 2. [Figure 20a] FIG. 13 is a graph showing a particle size distribution curve of the Cu powder in Comparative Example 3 superimposed on a particle size distribution curve of a composite filler obtained by mixing the Cu powder and fumed alumina particles in a dry ball mill. [Figure 20b] FIG. 2 is a scanning electron microscope (SEM) photograph of the Cu powder of Comparative Example 3. [Figure 20c] FIG. 2 is a scanning electron microscope (SEM) photograph of the composite filler of Comparative Example 3. [Figure 21a] FIG. 13 is a graph showing a particle size distribution curve of the Cu powder in Comparative Example 4 superimposed on a particle size distribution curve of a composite filler obtained by mixing the Cu powder and fumed alumina particles in a dry ball mill. [Figure 21b] FIG. 1 is a scanning electron microscope (SEM) photograph of the Cu powder of Comparative Example 4. [Figure 21c] FIG. 1 is a scanning electron microscope (SEM) photograph of the composite filler of Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Next, an embodiment of the present invention will be described with reference to the drawings. As shown in Fig. 1, the composite filler 10 of the present embodiment forms a core-shell structure consisting of a core material 11 made of carbon, metal, zinc oxide, or zirconium oxide, and a shell material 12 attached to the surface of the core material 11. In Fig. 1, the shell material 12 is attached to the entire surface of the core material 11, but it may be attached to a part of the surface of the core material 11. Also, Fig. 1 shows an example in which the shape of the core material 11 is spherical, but the core material is not limited to being spherical, and may be a needle, rod, or flat plate.

[0023] When the core material 10 is carbon, examples of the carbon include graphite, ketjen black, graphite, and carbon black. When the core material is metal, examples of the metal include copper, zinc, tin, nickel, aluminum, and stainless steel. Zinc oxide or zirconium oxide is selected as the core material because it has a high thermal conductivity equivalent to that of metals. The particle size and particle size distribution of the core material cannot be determined in general because they differ depending on the material of carbon, metal, or zinc oxide or zirconium oxide and the manufacturing method thereof.

[0024] The shell material 12 of the present embodiment is formed by mixing the fumed oxide particles and the core material in a dry ball mill at room temperature, so that the fumed oxide particles adhere to the surface of the core material. Examples of the fumed oxide particles include fumed silica particles or fumed alumina particles. The fumed oxide particles include hydrophilic fumed oxide particles and hydrophobic fumed oxide particles. The average primary particle size of the fumed oxide particles is measured by image analysis using a transmission electron microscope (TEM) and is in the range of 7 nm to 90 nm. When the fumed oxide particles and the core material are mixed by a dry hand mixing method or a dry rotation-revolution type mixer, which are methods other than the dry ball mill, the adhesion of the shell material to the core material is insufficient, and a composite filler having the desired thermal conductivity and electrical insulation properties cannot be obtained. As shown in the enlarged view of FIG. 1, the shell material 12 is formed including agglomerated particles 12a and voids 12b between the agglomerated particles.

[0025] When the fumed oxide particles and the core material are mixed in a dry ball mill at room temperature, the agglomerated particles of the fumed oxide particles are coated and attached to the core material, and the core material itself may become smaller in diameter, or the smaller core materials may aggregate together. Therefore, when the particle size of the composite filler is examined using a particle size distribution curve, the peak diameter in the particle size distribution is not limited to one, but may appear to be multiple peak diameters. For this reason, the average particle size of the composite filler cannot be determined in general, but from the particle size distribution curves in Examples 1 to 13 described later, the particle size of the composite filler is in the range of 1 μm to 300 μm. For the same reason that the average particle size of the composite filler cannot be determined in general, the average particle size of the shell material in the composite filler cannot be determined in general either. However, the average particle size of the core material is on the order of microns (μm), while the average particle size of the shell material is on the order of nanometers (nm). Considering the peak diameter of the core material before compounding and the main peak diameter of the composite filler in Examples 1 to 13 described later, the thickness of the shell material layer, which can be estimated from the particle size distribution curve, is calculated to be in the range of 3 μm to 20 μm. The thickness of this shell material layer is twice the "d" shown in FIG.

[0026] As shown in FIG. 2, when the fumed oxide particles are fumed silica particles, the agglomerated particles 12a are formed by injecting a mixed gas of SiCl4, H2, and O2 as vaporization raw materials from a reactor, which is a burner, and the primary particles are sintered to form agglomerated particles, which are the smallest particle form. The agglomerated particles then gather together through weak interactions such as hydrogen bonds and van der Waals forces to form agglomerated particles. In an aggregate of a plurality of composite fillers, the shell material is densely packed between the core materials, forming a three-dimensional network structure that densely fills the gaps between the core materials. As a result, the volume resistivity of the composite filler as an aggregate can be increased to 1.0×10 without impairing the high thermal conductivity of the core material. 5The dielectric constant can be increased to more than Ω·cm and the breakdown voltage can be increased to more than 1kV / mm. This allows the core material to achieve high electrical insulation while maintaining its inherent high thermal conductivity. Figure 3 shows the aggregate particles, which are the smallest particle form formed by sintering primary particles, and Figure 4 shows the agglomerated particles formed by the aggregate particles gathering together through weak interactions such as hydrogen bonds and van der Waals forces.

[0027] When the composite filler is 100% by volume, the core material is in the range of 30% by volume to 85% by volume, and the shell material is in the range of 15% by volume to 70% by volume. The core material is preferably in the range of 30% by volume to 70% by volume, and the shell material is preferably in the range of 30% by volume to 70% by volume. If the core material is less than 30% by volume and the shell material is more than 70% by volume, a composite filler having a desired thermal conductivity cannot be obtained. If the core material is more than 85% by volume and the shell material is less than 15% by volume, a composite filler having a desired volume resistivity and breakdown voltage cannot be obtained. The shell material formed by including agglomerated particles 12a made of fumed oxide particles and voids 12 (see the enlarged view of FIG. 1) is attached to the surface of the core material at a predetermined volume % by mixing with a dry ball mill, so that the composite filler of this embodiment maintains high thermal conductivity and has high volume resistivity and high breakdown voltage.

[0028] The composite filler of this embodiment is characterized in that its thermal conductivity is 0.075 W / m·K or more, preferably 0.100 W / m·K or more, when measured under maximum compressive load conditions (2400.0 gF) using a thermal conductivity measuring device TRIDENT and a compression test accessory (CTA) manufactured by C-Therm. The composite filler of this embodiment also has a volume resistivity of 1.0×10 or more, when measured using a high resistance / resistivity meter "Hiresta-UX" (manufactured by Mitsubishi Chemical Analytech Co., Ltd.: model number "MCP-HT800") or a low resistance / resistivity meter "Loresta-GX" (manufactured by Mitsubishi Chemical Analytech Co., Ltd.: model number "MCP-T700") and a powder resistivity measuring system (manufactured by Mitsubishi Chemical Analytech Co., Ltd.: model number "MCP-PD-51"). 5Ω cm or more, preferably 2.0×10 5 Furthermore, the composite filler of the present embodiment is characterized in that its dielectric breakdown voltage is 1 kV / mm or more, preferably 2 kV / mm or more, when measured using an AC Withstand Voltage Tester 7473 manufactured by Keisoku Gijutsu Kenkyusho Co., Ltd.

[0029] The thermal conductivity and volume resistivity are values ​​measured when the powder composite filler is used. The dielectric breakdown voltage is measured when a resin mixture is prepared by mixing 63 volume % of silicone resin (manufactured by Momentive Corp.: model number "YE5822A"), 7 volume % of hardener (manufactured by Momentive Corp.: model number "YE5822B"), and 30 volume % of composite filler, and the resin mixture and composite filler are mixed at 2000 rpm for 5 minutes in a rotation-revolution mixer (manufactured by Thinky Corp.: model number "ARE-310") to prepare a resin composition, and then the resin composition is placed in a mold with a cavity of length x width x depth of 15 cm x 15 cm x 2 mm, and the resin is cured by applying a pressure of 10 MPa (100 kg / cm2) at a temperature of 130°C and holding the pressure for 10 minutes in a heat press (manufactured by Kodaira Seisakusho Co., Ltd.: model number "PY15-EA") to the resin molded body. EXAMPLES

[0030] Next, examples of the present invention will be described in detail together with comparative examples.

[0031] The raw materials used in the examples and comparative examples of the present invention are as follows. The following raw materials were used as commercially available: (1) Tin powder (Sn, Fujifilm Wako Pure Chemical Industries, Ltd.: product number "206-01505") (2) Hydrophilic fumed alumina particles (Al2O3, manufactured by Evonik Corporation: product number "AEROXIDE (registered trademark) Alu C" (average primary particle size 13 nm)) (3) Zinc powder (Zn, manufactured by Hayashi Pure Chemical Industries, Ltd.: product number "26000085") (4) Nickel powder (Ni, Fujifilm Wako Pure Chemical Industries, Ltd.: Part number "145-00982") (5) Stainless steel powder (SUS, Fujifilm Wako Pure Chemical Industries, Ltd.: product number "900919") (6) Zinc oxide powder (ZnO, manufactured by Hayashi Pure Chemical Industries, Ltd.: product number "26000375") (7) Copper powder (Cu, manufactured by Hayashi Pure Chemical Industries, Ltd.: product number "03003695") (8) Hydrophilic fumed alumina particles (Al2O3, manufactured by Evonik Corporation: product number "VP Alu 30" (average primary particle size 90 nm)) (9) Hydrophobic fumed alumina particles (Al2O3, manufactured by Nippon Aerosil Co., Ltd.: product number "VP Alu C RK" (average primary particle size 13 nm)) (10) Isobutyltrimethoxysilane (IBTMO, manufactured by Evonik Corporation: product number "Dynasylan (registered trademark) IBTMO") (11) Aluminum powder (Al, manufactured by Hayashi Pure Chemical Industries, Ltd.: product number "01001325") (12) Zirconium oxide powder (ZrO, Fujifilm Wako Pure Chemical Industries, Ltd.: Part number "264-00485") (13) Graphite powder (C, manufactured by Ito Graphite Industries Co., Ltd.: product number "SG-BL40") (14) Hydrophilic fumed silica particles (manufactured by Nippon Aerosil Co., Ltd.: product number "AEROSIL (registered trademark) 380S" (average primary particle size 7 nm))

[0032] <Example 1> As the core material, Sn (tin) powder was prepared, which has one peak particle size of 17 μm in the particle size distribution as shown in FIG. 5a, and has a 10% cumulative volume of 9.6 μm, a 50% cumulative volume of 18.4 μm, and a 90% cumulative volume of 40.6 μm as shown in Table 1, calculated from the small diameter side. In addition, hydrophilic fumed alumina particles (product number "AEROXIDE (registered trademark) Alu C") were prepared as the shell material. Next, 30% by volume of the core material (Sn powder) and 70% by volume of the shell material (fumed alumina particles) were dry-mixed on a ball mill turntable (manufactured by Masuda Rika Kogyo Co., Ltd.: model number "UNIVERSAL BALL MILL MODEL UBM-S") by rotating a pot mill containing alumina balls with a diameter of 5 mm manufactured by Nikkato Corporation at room temperature in the air at a speed of 110 rpm for 5 hours to obtain a composite filler. As shown in Figure 5a, the particle size distribution of this composite filler has two peaks, at particle sizes of 12 μm and 67 μm. As shown in Table 1, the particle size distribution of this composite filler shows that the particle size at 10% of the cumulative volume calculated from the small diameter side is 5.9 μm, the particle size at 50% is 15.7 μm, and the particle size at 90% is 89.3 μm. Since the particle size range of the Sn powder in the particle size distribution was wide, from 4 μm to 150 μm, it was difficult to calculate the thickness of the shell material layer. Figure 5b shows a scanning electron microscope (SEM) photograph of the Sn powder, and Figure 5c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0033] [Table 1]

[0034] The particle size of the core material or composite filler in Example 1 and other Examples and Comparative Examples described below is the particle size in a particle size distribution curve obtained by measuring the core material or composite filler using a laser diffraction / scattering type particle size distribution measuring device (manufactured by Horiba, Ltd., model "LA960") and plotting the particle size of the obtained core material or composite filler on the horizontal axis and the frequency of particles converted into volume on the vertical axis. The average primary particle size of the shell material is the particle size measured by image analysis using a transmission electron microscope (TEM).

[0035] <Example 2> As the core material, Zn (zinc) powder was prepared, which has one peak particle size of 9 μm in the particle size distribution as shown in FIG. 6a, and has a 10% cumulative volume of 5.2 μm, a 50% cumulative volume of 8.0 μm, and a 90% cumulative volume of 12.2 μm as shown in Table 2, calculated from the small diameter side. In addition, the same hydrophilic fumed alumina particles (product number "AEROXIDE (registered trademark) Alu C") as in Example 1 were prepared as the shell material. Next, 30 volume % of the core material (Zn powder) and 70 volume % of the shell material (fumed alumina particles) were dry mixed in the same manner as in Example 1 using the same dry ball mill as in Example 1 to obtain a composite filler. As shown in Figure 6a, the particle size distribution of this composite filler has two peaks, at particle sizes of 12 μm and 67 μm. As shown in Table 2, the particle size distribution of this composite filler shows that the particle size at 10% of the cumulative volume calculated from the small diameter side is 5.1 μm, the particle size at 50% is 12.2 μm, and the particle size at 90% is 50.4 μm. Since the particle size range of the Zn powder in the particle size distribution was relatively narrow, from 3 μm to 22 μm, the thickness of the shell material layer was estimated to be 3 μm, i.e., 12 μm-9 μm. Figure 6b shows a scanning electron microscope (SEM) photograph of the Zn powder, and Figure 6c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0036] [Table 2]

[0037] <Example 3> As the core material, Ni (nickel) powder was prepared, which has one peak particle size of 10 μm in the particle size distribution as shown in FIG. 7a, and has a 10% cumulative volume of 5.6 μm, a 50% cumulative volume of 9.6 μm, and a 90% cumulative volume of 16.5 μm as shown in Table 3, calculated from the small diameter side. In addition, the same hydrophilic fumed alumina particles (product number "AEROXIDE (registered trademark) Alu C") as in Example 1 were prepared as the shell material. Next, 30 volume % of the core material (Ni powder) and 70 volume % of the shell material (fumed alumina particles) were dry mixed in the same manner as in Example 1 using the same dry ball mill as in Example 1 to obtain a composite filler. The particle size distribution peak of this composite filler is one with a particle size of 12μm, as shown in Figure 7a, and as shown in Table 3, the particle size distribution of this composite filler is 3.3μm at 10% of the cumulative volume calculated from the small diameter side, 9.2μm at 50% of the cumulative volume, and 38.4μm at 90% of the cumulative volume. Since the particle size of the Ni powder in the particle size distribution was in a relatively narrow range from 3μm to 30μm, the thickness of the shell material layer was estimated to be 2μm, i.e., 12μm-10μm. Figure 7b shows a scanning electron microscope (SEM) photograph of the Ni powder, and Figure 7c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0038] [Table 3]

[0039] <Example 4> As the core material, SUS (stainless steel) powder was prepared, which has one peak particle size of 89 μm in the particle size distribution as shown in FIG. 8a, and has a 10% cumulative volume of 26.0 μm, a 50% cumulative volume of 68.9 μm, and a 90% cumulative volume of 160.3 μm as shown in Table 4, calculated from the small diameter side. In addition, the same hydrophilic fumed alumina particles (product number "AEROXIDE (registered trademark) Alu C") as in Example 1 were prepared as the shell material. Next, 30 volume % of the core material (SUS powder) and 70 volume % of the shell material (fumed alumina particles) were dry mixed in the same manner as in Example 1 using the same dry ball mill as in Example 1 to obtain a composite filler. As shown in Figure 8a, the particle size distribution of this composite filler has two peaks, at particle sizes of 12 μm and 67 μm. As shown in Table 4, the particle size distribution of this composite filler is 5.8 μm at 10% of the cumulative volume calculated from the small diameter side, 13.4 μm at 50% of the cumulative volume, and 57.6 μm at 90% of the cumulative volume. Since the particle size range of the SUS powder in the particle size distribution was wide, from 8 μm to 300 μm, it was difficult to calculate the thickness of the shell material layer. Figure 8b shows a scanning electron microscope (SEM) photograph of the SUS powder, and Figure 8c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0040] [Table 4]

[0041] <Example 5> As the core material, ZnO (zinc oxide) powder was prepared, which has three peak particle sizes of 0.09 μm, 2 μm, and 77 μm in the particle size distribution as shown in FIG. 9a, and has a 10% cumulative volume of 0.6 μm, a 50% cumulative volume of 2.6 μm, and a 90% cumulative volume of 38.9 μm as shown in Table 5, calculated from the small diameter side. In addition, the same hydrophilic fumed alumina particles (product number "AEROXIDE (registered trademark) Alu C") as in Example 1 were prepared as the shell material. Next, 30 volume % of the core material (ZnO powder) and 70 volume % of the shell material (fumed alumina particles) were dry mixed in the same manner as in Example 1 using the same dry ball mill as in Example 1 to obtain a composite filler. As shown in Figure 9a, the particle size distribution of this composite filler has two peaks, at particle sizes of 13 μm and 45 μm. As shown in Table 5, the particle size distribution of this composite filler is 1.7 μm at 10% of the cumulative volume calculated from the small diameter side, 14.5 μm at 50% of the cumulative volume, and 63.3 μm at 90% of the cumulative volume. Since the particle size range of the ZnO powder in the particle size distribution was wide, from 0.06 μm to 300 μm, it was difficult to calculate the thickness of the shell material layer. Figure 9b shows a scanning electron microscope (SEM) photograph of the ZnO powder, and Figure 9c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0042] [Table 5]

[0043] <Example 6> As the core material, Cu (copper) powder was prepared, which has one peak particle size of 34 μm in the particle size distribution as shown in FIG. 10a, and has a 10% cumulative volume of 13.5 μm, a 50% cumulative volume of 30.6 μm, and a 90% cumulative volume of 62.0 μm as shown in Table 6, calculated from the small diameter side. In addition, the same hydrophilic fumed alumina particles (product number "AEROXIDE (registered trademark) Alu C") as in Example 1 were prepared as the shell material. Next, 30 volume % of the core material (Cu powder) and 70 volume % of the shell material (fumed alumina particles) were dry mixed in the same manner as in Example 1 using the same dry ball mill as in Example 1 to obtain a composite filler. As shown in Figure 10a, the particle size distribution of this composite filler has two peaks, 13 μm and 51 μm. As shown in Table 6, the particle size distribution of this composite filler is 6.8 μm at 10% of the cumulative volume calculated from the small diameter side, 16.4 μm at 50% of the cumulative volume, and 66.3 μm at 90% of the cumulative volume. Since the particle size of the Cu powder in the particle size distribution ranged from 5 μm to 175 μm, it was difficult to calculate the thickness of the shell material layer, but for convenience, the thickness of the shell material layer was estimated to be 17 μm, which is 51 μm-34 μm. Figure 10b shows a scanning electron microscope (SEM) photograph of the Cu powder, and Figure 10c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0044] [Table 6]

[0045] <Example 7> As the core material, the same Cu (copper) powder as in Example 6 was prepared, which has one peak particle size of 34 μm in the particle size distribution as shown in FIG. 11a, and has a 10% cumulative volume of 13.5 μm, a 50% cumulative volume of 30.6 μm, and a 90% cumulative volume of 62.0 μm as shown in Table 7, calculated from the small diameter side. In addition, hydrophilic fumed alumina particles (product number "VP Alu 30") were prepared as the shell material. Next, 30 volume % of the core material (Cu powder) and 70 volume % of the shell material (fumed alumina particles) were dry mixed in the same manner as in Example 1 using the same dry ball mill as in Example 1 to obtain a composite filler. As shown in FIG. 11a, the particle size distribution of this composite filler has two peaks, 13 μm and 51 μm. As shown in Table 7, the particle size distribution of this composite filler is 6.8 μm at 10% of the cumulative volume calculated from the small diameter side, 16.4 μm at 50% and 66.3 μm at 90%, which is no different from Example 6. Since the particle size of the Cu powder in the particle size distribution ranged from 5 μm to 175 μm, it was difficult to calculate the thickness of the shell material layer, but for convenience, the thickness of the shell material layer was estimated to be 17 μm, which is 51 μm-34 μm. FIG. 11b shows a scanning electron microscope (SEM) photograph of the Cu powder, and FIG. 11c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0046] [Table 7]

[0047] <Example 8> As the core material, the same Cu (copper) powder as in Example 6 was prepared, which has one peak particle size of 34 μm in the particle size distribution as shown in FIG. 12a, and has a 10% cumulative volume of 13.5 μm, a 50% cumulative volume of 30.6 μm, and a 90% cumulative volume of 62.0 μm as shown in Table 8, calculated from the small diameter side. In addition, hydrophobic fumed alumina particles (product number "VP Alu C RK") were prepared as the shell material. Next, 30 volume % of the core material (Cu powder) and 70 volume % of the shell material (fumed alumina particles) were dry mixed in the same manner as in Example 1 using the same dry ball mill as in Example 1 to obtain a composite filler. The particle size distribution peak of this composite filler is 12μm as shown in Figure 12a. As shown in Table 8, the particle size distribution of this composite filler is 2.6μm at 10% of the cumulative volume calculated from the small diameter side, 9.2μm at 50% of the cumulative volume, and 26.5μm at 90% of the cumulative volume. The particle size distribution of Cu powder was in a wide range from 5μm to 175μm, so it was difficult to calculate the thickness of the shell material layer. Figure 12b shows a scanning electron microscope (SEM) photograph of Cu powder, and Figure 12c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0048] [Table 8]

[0049] <Example 9> As the core material, the same Cu (copper) powder as in Example 6 was prepared, which has one peak particle size of 34 μm in the particle size distribution as shown in FIG. 13a, and has a 10% cumulative volume of 13.5 μm, a 50% cumulative volume of 30.6 μm, and a 90% cumulative volume of 62.0 μm as shown in Table 9, calculated from the small diameter side. In addition, hydrophilic fumed alumina particles (product number "AEROXIDE (registered trademark) Alu C") were prepared as the shell material. Next, 70 volume % of the core material (Cu powder) and 30 volume % of the shell material (fumed alumina particles) were dry mixed in the same manner as in Example 1 using the same dry ball mill as in Example 1 to obtain a composite filler. As shown in Figure 13a, the particle size distribution of this composite filler has two peaks, 13μm and 45μm. As shown in Table 9, the particle size distribution of this composite filler is 7.3μm at 10% of the cumulative volume calculated from the small diameter side, 17.2μm at 50% of the cumulative volume, and 55.7μm at 90% of the cumulative volume. Since the particle size of the Cu powder was in a wide range from 5μm to 175μm, it was difficult to calculate the thickness of the shell material layer, but for convenience, the thickness of the shell material layer was estimated to be 11μm, which is 45μm-34μm. Figure 13b shows a scanning electron microscope (SEM) photograph of the Cu powder, and Figure 13c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0050] [Table 9]

[0051] <Example 10> As the core material, the same Cu (copper) powder as in Example 6 was prepared, which has one peak particle size of 34 μm in the particle size distribution as shown in FIG. 14a, and has a 10% cumulative volume of 13.5 μm, a 50% cumulative volume of 30.6 μm, and a 90% cumulative volume of 62.0 μm as shown in Table 10, calculated from the small diameter side. In addition, the same hydrophilic fumed alumina particles (product number "AEROXIDE (registered trademark) Alu C") as in Example 1 were prepared as the shell material. Next, 30 volume % of the core material (Cu powder) and 70 volume % of the shell material (fumed alumina particles) were dry mixed in the same manner as in Example 1 using the same dry ball mill as in Example 1, and then the surface of this mixed powder was hydrophobized by wet treatment with isobutyltrimethoxysilane, a silane coupling agent (hereinafter referred to as C4 treatment) to obtain a composite filler. In this C4 process, the mixed powder is put into a beaker containing IBTMO, heated in the air at 120°C using a magnetic stirrer with a hot plate (Tokyo Rika Kikai Co., Ltd.: Model No. RH-1000), and then dried in the air at 150°C for 1 hour. The dried product was used as the composite filler. As shown in Figure 14a, the particle size distribution of this composite filler has three peaks at particle sizes of 15 μm, 51 μm, and 300 μm. As shown in Table 10, the particle size distribution of this composite filler is 8.2 μm at 10% of the cumulative volume calculated from the small diameter side, 40.3 μm at 50%, and 298.9 μm at 90%. Since the particle size of the Cu powder was in a wide range from 5 μm to 175 μm, it was difficult to calculate the thickness of the shell material layer, but for convenience, the thickness of the shell material layer was estimated to be 17 μm (51 μm-34 μm). Figure 14b shows a scanning electron microscope (SEM) photograph of the Cu powder, and Figure 14c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0052] [Table 10]

[0053] <Example 11> As the core material, an Al (aluminum) powder was prepared, which has one peak particle size of 30 μm in the particle size distribution as shown in FIG. 15a, and has a 10% cumulative volume of 20.3 μm, a 50% cumulative volume of 30.2 μm, and a 90% cumulative volume of 47.9 μm as shown in Table 11, calculated from the small diameter side. In addition, the same hydrophilic fumed alumina particles (product number "AEROXIDE (registered trademark) Alu C") as in Example 1 were prepared as the shell material. Next, 85 volume % of the core material (Al powder) and 15 volume % of the shell material (fumed alumina particles) were dry mixed in the same manner as in Example 1 using the same dry ball mill as in Example 1 to obtain a composite filler. The particle size distribution peak of this composite filler is one with a particle size of 45μm, as shown in Figure 15a, and as shown in Table 11, the particle size distribution of this composite filler is 10.2μm, 50% of the cumulative volume is 35.3μm, and 90% of the cumulative volume is 60.1μm, calculated from the small diameter side. Since the particle size of the Al powder in the particle size distribution was in a relatively narrow range from 12μm to 77μm, the thickness of the shell material layer was estimated to be 15μm, which is 45μm-30μm. Figure 15b shows a scanning electron microscope (SEM) photograph of the Al powder, and Figure 15c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0054] [Table 11]

[0055] <Example 12> As the core material, ZrO (zirconium oxide) powder was prepared, which has one peak particle size of 45 μm in the particle size distribution as shown in FIG. 16a, and has a 10% cumulative volume of 2.0 μm, a 50% cumulative volume of 35.9 μm, and a 90% cumulative volume of 65.1 μm as shown in Table 12, calculated from the small diameter side. In addition, the same hydrophilic fumed alumina particles (product number "AEROXIDE (registered trademark) Alu C") as in Example 1 were prepared as the shell material. Next, 30 volume % of the core material (ZrO powder) and 70 volume % of the shell material (fumed alumina particles) were dry mixed in the same manner as in Example 1 using the same dry ball mill as in Example 1 to obtain a composite filler. As shown in Figure 16a, the particle size distribution of this composite filler has two peaks, 12 μm and 59 μm. As shown in Table 12, the particle size distribution of this composite filler is 3.2 μm at 10% of the cumulative volume calculated from the small diameter side, 11.4 μm at 50% of the cumulative volume, and 52.7 μm at 90% of the cumulative volume. Since the particle size distribution of the ZrO powder was in a relatively wide range from 0.2 μm to 150 μm, it was difficult to calculate the thickness of the shell material layer, but for convenience, the thickness of the shell material layer was estimated to be 14 μm, that is, 59 μm-45 μm. Figure 16b shows a scanning electron microscope (SEM) photograph of the ZrO powder, and Figure 16c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0056] [Table 12]

[0057] <Example 13> As the core material, graphite powder was prepared, which has one peak particle size of 39 μm in the particle size distribution as shown in FIG. 17a, and has a 10% cumulative volume of 15.8 μm, a 50% cumulative volume of 34.2 μm, and a 90% cumulative volume of 57.9 μm as shown in Table 13, calculated from the small diameter side. In addition, hydrophilic fumed silica particles (product number "AEROSIL (registered trademark) 380S") were prepared as the shell material. Next, 30 volume % of the core material (graphite powder) and 70 volume % of the shell material (fumed silica particles) were dry mixed in the same manner as in Example 1 using the same dry ball mill as in Example 1 to obtain a composite filler. As shown in Figure 17a, the particle size distribution of this composite filler has two peaks, 12μm and 59μm. As shown in Table 13, the particle size distribution of this composite filler is 5.3μm at 10% of the cumulative volume calculated from the small diameter side, 18.3μm at 50% and 76.7μm at 90%. Since the particle size range of the graphite powder in the particle size distribution was relatively wide, from 4μm to 101μm, it was difficult to calculate the thickness of the shell material layer, but for convenience, the thickness of the shell material layer was estimated to be 20μm, i.e., 59μm-39μm. Figure 17b shows a scanning electron microscope (SEM) photograph of the graphite powder, and Figure 17c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0058] [Table 13]

[0059] <Comparative Example 1> As the core material, the same Cu (copper) powder as in Example 6 was prepared, which has one peak particle size of 34 μm in the particle size distribution as shown in FIG. 18a, and has a 10% cumulative volume of 13.5 μm, a 50% cumulative volume of 30.6 μm, and a 90% cumulative volume of 62.0 μm as shown in Table 14, calculated from the small diameter side. In addition, the same hydrophilic fumed alumina particles (product number "AEROXIDE (registered trademark) Alu C") as in Example 1 were prepared as the shell material. Next, 30 volume % of the core material (Cu powder) and 70 volume % of the shell material (fumed alumina particles) were placed in a polyethylene bag in the air, and the polyethylene bag was mixed with a gloved hand for 1 minute to obtain a composite filler by a hand mixing method. The particle size distribution of this composite filler had a single peak at a particle size of 12 μm, as shown in Figure 18a. As shown in Table 14, the particle size distribution of this composite filler was 6.7 μm at 10% of the cumulative volume calculated from the small diameter side, 11.4 μm at 50%, and 20.4 μm at 90%. The particle size distribution of the composite filler after hand mixing had a sharp single peak, and it was thought that the core material Cu powder had become agglomerates weak enough to be broken up by hand mixing, making it difficult to calculate the thickness of the shell material layer. Figure 18b shows a scanning electron microscope (SEM) photograph of the Cu powder, and Figure 18c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0060] [Table 14]

[0061] <Comparative Example 2> As the core material, the same Cu (copper) powder as in Example 6 was prepared, which has one peak particle size of 34 μm in the particle size distribution as shown in FIG. 19a, and has a 10% cumulative volume of 13.5 μm, a 50% cumulative volume of 30.6 μm, and a 90% cumulative volume of 62.0 μm as shown in Table 15, calculated from the small diameter side. In addition, the same hydrophilic fumed alumina particles (product number "AEROXIDE (registered trademark) Alu C") as in Example 1 were prepared as the shell material. Next, 30 volume % of the core material (Cu powder) and 70 volume % of the shell material (fumed alumina particles) were mixed in air at 2000 rpm for 3 minutes in a rotation-revolution type mixer (Thinki Corporation, Awatori Rentaro: model number "ARE-310") to obtain a composite filler. As shown in Figure 19a, the particle size distribution of this composite filler has two peaks, 13 μm and 67 μm. As shown in Table 15, the particle size distribution of this composite filler is 11.2 μm at 10% of the cumulative volume calculated from the small diameter side, 51.2 μm at 50% and 91.9 μm at 90%. Since the peak diameter of 67 μm was the main diameter in the particle size distribution of the composite filler and there was a significant difference from Example 6, which was composited using a dry ball mill, the thickness of the shell material layer was estimated to be 33 μm, i.e., 67 μm-34 μm. Figure 19b shows a scanning electron microscope (SEM) photograph of the Cu powder, and Figure 19c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0062] [Table 15]

[0063] <Comparative Example 3> As the core material, the same copper (Cu) powder as in Example 6 was prepared, which has one peak particle size of 34 μm in the particle size distribution as shown in FIG. 20a, and has a cumulative volume percentage calculated from the small diameter side of 10% particle size of 13.5 μm, 50% particle size of 30.6 μm, and 90% particle size of 62.0 μm as shown in Table 16. As the shell material, the same hydrophilic fumed alumina particles (product number "AEROXIDE (registered trademark) Alu C") as in Example 1 were prepared. Next, 25 volume % of the core material (Cu powder) and 75 volume % of the shell material (fumed alumina particles) were dry mixed in the same manner as in Example 1 using the same dry ball mill as in Example 1 to obtain a composite filler. As shown in Figure 20a, the particle size distribution of this composite filler has two peaks, 13 μm and 59 μm. As shown in Table 16, the particle size distribution of this composite filler is 4.1 μm at 10% of the cumulative volume calculated from the small diameter side, 13.8 μm at 50% of the cumulative volume, and 71.0 μm at 90% of the cumulative volume. Since the particle size of the Cu powder in the particle size distribution ranged from 5 μm to 175 μm, it was difficult to calculate the thickness of the shell material layer, but for convenience, the thickness of the shell material layer was estimated to be 25 μm, i.e., 59 μm-34 μm. Figure 20b shows a scanning electron microscope (SEM) photograph of the Cu powder, and Figure 20c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0064] [Table 16]

[0065] <Comparative Example 4> As the core material, the same copper (Cu) powder as in Example 6 was prepared, which has one peak particle size of 34 μm in the particle size distribution as shown in FIG. 21a, and has a cumulative volume percentage calculated from the small diameter side of 10% particle size of 13.5 μm, 50% particle size of 30.6 μm, and 90% particle size of 62.0 μm as shown in Table 17. As the shell material, the same hydrophilic fumed alumina particles (product number "AEROXIDE (registered trademark) Alu C") as in Example 1 were prepared. Next, 90 volume % of the core material (Cu powder) and 10 volume % of the shell material (fumed alumina particles) were dry mixed in the same manner as in Example 1 using the same dry ball mill as in Example 1 to obtain a composite filler. The particle size distribution of this composite filler had a single peak at a particle size of 30 μm, as shown in Figure 21a. As shown in Table 17, the particle size distribution of this composite filler was 14.0 μm at 10% of the cumulative volume calculated from the small diameter side, 27.1 μm at 50% of the cumulative volume, and 50.2 μm at 90% of the cumulative volume. The particle size distribution of the composite filler after mixing was a single sharp peak that was somewhat shifted to the small diameter side, making it difficult to calculate the thickness of the shell material. Figure 21b shows a scanning electron microscope (SEM) photograph of the Cu powder, and Figure 21c shows a scanning electron microscope (SEM) photograph of the composite filler.

[0066] [Table 17]

[0067] <Comparative Example 5> As in Example 6, a filler consisting only of Cu (copper) powder as a core material was prepared.

[0068] <Comparative Example 6> As in Example 11, a filler consisting of only Al (aluminum) powder was prepared.

[0069] <Comparative Example 7> As in Example 1, a filler consisting of only Sn (tin) powder was prepared.

[0070] The contents of the core materials and shell materials in the above-mentioned Examples 1 to 13 and Comparative Examples 1 to 4, and the methods of mixing these materials, are shown in Table 18. The compositions and physical properties of the composite fillers are shown in Table 19. Note that the fillers in Comparative Examples 5 to 7 consist only of uncomposite core materials, but are referred to as composite fillers for convenience.

[0071] [Table 18]

[0072] [Table 19]

[0073] <Comparative measurement of physical properties> The thermal conductivity of each of the composite fillers of Examples 1 to 13 and Comparative Examples 1 to 4, and the fillers of Comparative Examples 5 to 7 was measured using the above-mentioned device. 6 For values ​​of Ω·cm or more, use a high resistance resistivity meter and powder resistance measurement system. 6 When the dielectric strength was less than Ω·cm, a low-resistance resistivity meter and a powder resistance measurement system were used to measure the dielectric breakdown voltages of the composite fillers and the resin molded articles produced using the fillers by the method described above, using the devices described above. These results are shown in Table 19. Table 19 also shows the thermal conductivity ratios of Examples 1 to 13 and Comparative Examples 1 to 4, 6, and 7 when the thermal conductivity of the filler made of Cu powder in Comparative Example 5 is standardized to 100.

[0074] <Evaluation> As is clear from Tables 18 and 19, in the composite filler of Comparative Example 1 in which the core material and the shell material were mixed by hand without using the dry ball mill mixing method, the volume resistivity was measured in a compressed state by applying pressure to the powder, so that the volume resistivity was 1.9 × 10 6Although the value obtained is seemingly high at Ω·cm, in reality the mixing force is significantly insufficient, so the shell does not form, and the compatibility with the resin is very poor, making it difficult to produce a molded body and making it impossible to measure the breakdown voltage. Furthermore, the composite filler of Comparative Example 2, in which the core material and shell material were mixed using a rotation-revolution mixer rather than a dry ball mill mixing method, has a thicker shell material layer and many voids in the shell compared to the composite filler of Example 6, which was mixed using a dry ball mill, and has a volume resistivity of 2.9×10 2 It was low at Ω·cm.

[0075] In the composite filler of Comparative Example 3, in which the volume percent of the core material when mixed was 25 volume percent and the volume percent of the shell material was 75 volume percent, which is not within the appropriate range, the shell material was in excess relative to the core material, so the breakdown voltage was high at 5.0 kV / mm, but the thermal conductivity was low at 0.070 W / m K. In the composite filler of Comparative Example 4, in which the volume percent of the core material when mixed was 90 volume percent and the volume percent of the shell material was 10 volume percent, which is not within the appropriate range, the thermal conductivity was high at 0.112 W / m K, but the amount of shell material was insufficient to provide appropriate insulation, so the volume resistivity was low at 2.6 × 10 -3 The dielectric strength was low at only Ω·cm, and the dielectric breakdown voltage was remarkably low at 0 kV / mm.

[0076] The filler of Comparative Example 5, which was made only of the core material of Cu powder, had a high and excellent thermal conductivity of 0.126 W / m K, but the volume resistivity was 1.8 × 10 -4 The filler of Comparative Example 6, which was made only of the core material of Al powder, had a high and excellent thermal conductivity of 0.191 W / m K, but a low volume resistivity of 1.4 × 10 -4 The filler of Comparative Example 7, which was made only of the Sn powder core material, had a high and excellent thermal conductivity of 0.181 W / m K, but a low volume resistivity of 1.0 × 10 -4 The dielectric strength was low at only Ω·cm, and the dielectric breakdown voltage was remarkably low at 0 kV / mm.

[0077] In contrast, the fumed oxide particles of the shell material are particles in which spherical primary particles are aggregated and fused to form bulky aggregate particles, and these aggregate particles are changed into agglomerated particles. The shell material and the core material are mixed in a dry ball mill, and when the composite filler is taken as 100 volume %, the core material is in the range of 30 volume % to 85 volume % and the shell material is in the range of 15 volume % to 70 volume %. In the composite fillers of Examples 1 to 13, the thermal conductivity is 0.075 W / m K or more and the volume resistivity is 1.0 × 10 5 The dielectric strength was Ω·cm or more, and the dielectric breakdown voltage was 1 kV / mm or more.

[0078] In particular, when comparing the thermal conductivity of the composite filler of Example 6 (Cu:fumed alumina particles=30 vol%:70 vol%) and the composite filler of Example 9 (Cu:fumed alumina particles=70 vol%:30 vol%) in which the core material (Cu powder) and shell material (fumed alumina particles) are the same but the volume percentages are different, Example 9, which contains a rich core material, had a high thermal conductivity of 0.128 W / m K, while Example 6, which contains a poor core material, had a low thermal conductivity of 0.086 W / m K.

[0079] Regarding the volume resistivity and the dielectric breakdown voltage, the volume resistivity and the dielectric breakdown voltage of Example 6, which is rich in the shell material, were 5.7×10 5 The volume resistivity and breakdown voltage of Example 9, in which the shell material was poor, were 7.6×10 6 The volume resistivity was higher in Example 9 than in Example 6, and the dielectric breakdown voltage was higher in Example 6 than in Example 9, which is a result that occurs frequently. The volume resistivity is measured not for the powder itself but for a sample compressed under high pressure, and the applied voltage is at most about 0.1 to 0.5 kV, so that the insulation properties are more reliably discussed using the dielectric breakdown voltage.

[0080] In addition, considering Example 10, in which a composite filler of the same material and volume percentage as the core material and shell material of Example 6 was subjected to C4 treatment, the thermal conductivity of Example 6 was 0.086 W / m K, while that of Example 10 was 0.105 W / m K, which was slightly higher. In addition, comparing the volume resistivity, the volume resistivity of Example 6 was 5.7×10 5 The volume resistivity of Example 10 was 1.9×10 7 Furthermore, in terms of dielectric breakdown voltage, the dielectric breakdown voltage of Example 6 was 4.6 kV / mm, while that of Example 10 was 1.3 kV / mm, which was lower. This is believed to be because the air at the core-shell interface and within the shell material layer was replaced by the C4 treatment of the composite filler.

[0081] Furthermore, in the composite filler of Example 8, in which the fumed oxide particles are hydrophobic fumed alumina particles, the volume resistivity is 3.6×10 10 The volume resistivity of the composite fillers in the other examples, in which the fumed oxide particles were hydrophilic, was higher than that of the hydrophobic fumed alumina particles, which is believed to be due to the higher volume resistivity of the hydrophobic fumed alumina particles than that of the hydrophilic fumed alumina particles. [Industrial Applicability]

[0082] The composite filler of the present invention can be used as a cooling member for a heat generating body such as a semiconductor chip, a transistor, a lithium ion secondary battery, or an LED light source in a communication device or an in-vehicle electronic device; a cooling member for a stator built into a motor housing; a cooling member for a power conversion device built into an inverter case; a heat dissipation member for heat generated in a sliding part or a rotating part of an actuator, etc.

Claims

1. A composite filler that forms a core-shell structure composed of a core material made of carbon, metal, zinc oxide, or zirconium oxide and a shell material attached to the surface of the core material, the shell material is formed by mixing fumed oxide particles with the core material in a dry ball mill, with the fumed oxide particles adhering to a part or all of the surface of the core material; The fumed oxide particles are particles in which spherical primary particles are aggregated and fused to form bulky aggregate particles, and the aggregate particles are transformed into agglomerated particles, When the composite filler is 100% by volume, the core material is in the range of 30% by volume to 85% by volume, and the shell material is in the range of 15% by volume to 70% by volume; The thermal conductivity measured under maximum compressive load conditions (2400.0 gF) using a thermal conductivity measuring device TRIDENT and a compression test accessory (CTA) manufactured by C-Therm is 0.075 W / m · K or more; The volume resistivity measured using a high resistance / resistivity meter "Hiresta-UX" (manufactured by Mitsubishi Chemical Analytech Co., Ltd.: model number "MCP-HT800") or a low resistance / resistivity meter "Loresta-GX" (manufactured by Mitsubishi Chemical Analytech Co., Ltd.: model number "MCP-T700") and a powder resistivity measurement system (manufactured by Mitsubishi Chemical Analytech Co., Ltd.: model number "MCP-PD-51") was 1.0 x 10 5 Ω cm or more, and A composite filler having a dielectric breakdown voltage of 1 kV / mm or more as measured using an AC WITHSTAND VOLTAGE TESTER 7473 manufactured by Keisoku Gijutsu Kenkyusho Co., Ltd.

2. 2. The composite filler according to claim 1, wherein the carbon core material is graphite, ketjen black, graphite or carbon black, and the metal core material is copper, zinc, tin, nickel, aluminum or stainless steel.

3. The particle size of the composite filler is measured using a laser diffraction / scattering type particle size distribution measuring device (manufactured by Horiba, Ltd., model "LA960"), and is in the range of 1 μm to 300 μm. The composite filler according to claim 1.

4. 2. The composite filler according to claim 1, wherein said fumed oxide particles are fumed silica particles or fumed alumina particles.

5. A method for producing a composite filler, comprising mixing fumed oxide particles in which spherical primary particles are agglomerated and fused together in a beaded shape to form bulky agglomerated particles, and the agglomerated particles are changed into agglomerate particles with a core material made of carbon, metal, zinc oxide or zirconium oxide in a volume ratio of fumed oxide particles:core material = 30 to 85:70 to 15 in a dry ball mill, thereby forming a core-shell structure in which the fumed oxide particles are attached as a shell material to a part or all of the surface of the core material, wherein the fumed oxide particles are particles in which spherical primary particles are agglomerated and fused together in a beaded shape to form bulky agglomerated particles, and the agglomerated particles are changed into agglomerate particles.

Citation Information

Patent Citations

  • Composite particle

    JP2015164106A

  • Method for treating powder and powder treated by said method

    JP2016041850A

  • Thermally conductive electrically insulating particles and compositions

    JP2017504177A

  • Filler and production method of the same, and high heat-conducting insulation material and production method of the same

    JP2020132827A

  • Voltage switchable dielectric material having bonded particle constituents

    US20120217450A1